Learning to negotiate reality: a strategy for teaching intercultural competencies - Ariane Berthoin Antal; Victor J. Friedman (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
Managers in a global business environment work with people who have different values, behavioral norms, and ways of perceiving reality. Team members bring their different national and professional backgrounds to the table, and suppliers and clients come from different corporate cultures. Consequently, intercultural competencies have become important for a wider range and larger number of people in business than ever before. In order to prepare students to become effective in the multiple cultural contexts they will face, business educators must clarify what constitutes intercultural competencies and how to develop them within the context of a business school classroom. In this paper we present the idea of learning to negotiate reality as a core intercultural competence and we describe an approach we designed and used for developing this competence at an international business school in Europe. – – Die Fähigkeit, mit Menschen aus unterschiedlichen nationalen, professionellen, ethnischen und organisationellen Kulturen zu arbeiten wird immer wichtiger. Sei es in Projektgruppen mit Mitgliedern aus verschiedenen Ländern und mehreren Funktionsbereichen, sei es in Verhandlungen mit Kunden und Lieferanten: kulturell geprägte Werte und Verhaltensnormen beeinflussen die Erwartungen über Ziele und Vorgehensweisen und können zu Missverständnissen und Konflikten führen. Interkulturelle Kompetenz, im Sinne der Fähigkeit, ein gemeinsames Verständnis einer Situation auszuhandeln (negotiating reality) gewinnt in Organisationen immer mehr an Bedeutung. Dieser Beitrag beschreibt wie diese Kompetenz im Rahmen eines drei- bis viertägigen Seminars entwickelt werden kann. Die relevanten Theorien werden dargestellt und an einem ausgewählten Fall illustrativ angewandt.
Keywords: 300; Multikulturell; Kompetenz; Unterricht; Theorie; Interkulturelles Management